'Europeanization' as a legitimation strategy of political parties: the cases of Ukraine and Georgia. Issue 3 (2nd July 2016) - Cianciara, Agnieszka K.
Abstract: This article's objective is to critically assess the top-down rational choice and sociological approaches to Europeanization, while advocating the 'usages of Europe' approach. I argue that both classic top-down perspectives do not adequately grasp the nature of Europeanization of political parties beyond member and candidate countries. Empirically, the analysis focuses on transnational cooperation of political parties from Ukraine and Georgia and stresses agency of domestic partisan actors seeking international and domestic legitimacy. It is argued that European party federations and parliamentary cooperation formats should not only be seen as channels of top-down Europeanization, but they should rather be conceptualized as resources that are used strategically by domestic political parties. Thus the article deals with the following question: To what extent and how channels of Europeanization have been used by national political parties from outside the European Union as resources serving to attain partisan goals, both in terms of domestic positioning and international legitimacy? Patterns of strategic and legitimating usage of European partisan and parliamentary resources depend on whether parties in question are in power or in opposition and whether they are more pro-European or more pro-Russian.